PKM Pelatihan Penggunaan Word Wall Sebagai Media Pembelajaran Interaktif untuk Guru SDN 155678 Hutanabolon 2 Kelurahan Hutanabolon Kecamatan Tukka Kabupaten Tapanuli Tengah - Panggabean, Yusi Tri Utari; Hanum, Rahmadiah; Nasution, Atika Aini; Hasugian, Paska Marto (ULEAD : Jurnal E-Pengabdian, 2024)
The utilization of Word Wall as an interactive learning media holds great potential to enhance learning effectiveness in classrooms. The objective of this service is to provide training to teachers on the concepts, implementation, and benefits of using Word Wall within the context of active learning. Training methods employed include theoretical sessions, practical demonstrations, and collaborative discussions aimed at building understanding and practical skills. eval_uation results indicate that this training effectively expands teachers' knowledge and skills in utilizing Word Wall as an interactive learning tool, actively supporting student learning. This study highlights the importance of developing teachers' abilities to leverage educational technology in creating stimulating and inclusive learning environments.